Efisiensi Alokatif Dan Ekonomis Usahatani Padi Organik Di Provinsi Lampung - Sri Handayani; Sri Puji Lestari; Dwi Eva Nirmagustina; Ni Siluh Putu Nuryanti (Jurnal Penelitian Pertanian Terapan, 2023)
Organic rice farming is a cultivation activity that is synonymous with labor-intensive activities. The use of internal inputs in organic rice farming requires time and effort to prepare. Organic farming is a low-cost farming activity because the use of internal inputs makes organic rice farming more profitable. The purpose of this study was to analyze the level of allocative and economic efficiency of organic rice farming in Lampung Province. Economic and allocative efficiency analysis is carried out by deriving the dual frontier cost function from the Cobb-Douglas Stochastic Frontier production function. The results showed that organic rice farming in Lampung Province was not allocatively efficient. Farmers have not maximized the use of organic seeds and pesticides, where both production factors have a low price allocation. Organic rice farming in Lampung Province is not yet economically efficient. Farmers have not received the maximum revenue from organic rice farming. Most of the organic rice harvested is consumed by farming families, so not all organic rice harvested generates income.